Application of SPSS Software in Statistical Learning to Improve Student Learning Outcomes - Suleman Murana; Rahimin Rahimin (Indo-MathEdu Intellectuals Journal, 2021)
The use of the SPSS 21 (Statistical Product and Service Solution) program in learning can assist students in conducting statistical data analysis. This research aims to find out the application of SPSS 21 program as a data processor in improving student learning outcomes in statistics material class XI SMK Muhammadiyah Ambon. This type of research uses Classroom Action Research, with the number of subjects used in the study amounting to 31 people. The instruments used in this study used tests and observations. Observation is used to find out the condition of the student learning process using the SPSS 21 program and test questions are used to find out the student learning results obtained after carrying out learning using the SPSS 21 program. The results of data analysis are known that learning using SPSS 21 is better when compared to the classical learning process. Student test results experienced an increase in learning results, namely on the initial test the average score obtained by students was 49.84 with a completion percentage of 16.13 percent, and increased in the implementation of cycle I tests where the learning process was carried out using SPSS 21 with an average score of 61.85 and a completion percentage of 61.29 percent, and increased again in the implementation of cycle II tests with an average score of 79.03 with a completion percentage of 90.32 percent.